Vocal communication of cetaceans (Cetacea) with emphasis on development and learning - Zvěřinová, Adéla (Univerzita Karlova, Přírodovědecká fakulta, 2021)
Vocal communication is the main mean of communication for cetaceans. Just like the species themselves, their repertoires are diverse, consisting of tonal, pulsed, and combined calls, with frequency and amplitude modulation. The two groups of cetaceans, Mysticeti (baleen whales) and Odontoceti (toothed whales), produce sounds of different parameters, mainly frequency, bandwidth, and duration. Both production and contextual learning can be found in cetaceans. It is used to acquire two types of sounds: signature calls and songs. Signature calls are present only in species living in stable groups or fission-fusion society. They are used as an identification tool to maintain cohesion and contact with conspecifics. Songs are present in most baleen whales, but only humpback and bowhead whales' change within and between seasons. They use vocal learning to conform to one type used by all individuals. It is also employed during vocal development in ontogenesis, together with maturation. Calves and juveniles' calls are chaotic, lacking in structure. With age, they gain stereotypy and resemble adults' repertoire. Key words: cetaceans, vocal communication, signature calls, vocal learning, cultural transmission Vokalizace je hlavním komunikačním prostředkem kytovců. Paleta zvuků, které kytovci vydávají je stejně rozmanitá jako jednotlivé druhy. Zahrnuje tonální i pulzní zvuky, a také jejich kombinace, často s různě modulovanou frekvencí a amplitudou. Zvuky vydávané kosticovci (Mysticeti) a ozubenými (Odontoceti) se liší v mnoha parametrech, především ve frekvenci, šířce frekvenčního spektra a doby trvání. U kytovců jsou známé obě formy učení zvuků, a to jak učení vydávání zvuků, tak i kontextu. Slouží k osvojení dvou typů zvuků: tzv. signature calls a písní. Signature calls najdeme pouze u druhů žijících v stálých skupinách nebo societách typu fission-fussion. Jsou používány jako identifikační nástroj k udržení soudržnosti a kontaktu s ostatními jedinci. Písně se nachází v repertoáru většiny kosticovců, ale pouze u velryby ...